KOTA BARU: KAJIAN AWAL TENTANG KAWASAN DI YOGYAKARTA - Supangat, Surayati; Setianingsih, Rita M. (Berkala Arkeologi, 1995)
In the early 20th century, European "settlements" were opened, located north of the city of Yogyakarta, which is now known as Kota Baru. The settlement was an extension of the city of Yogyakarta for the Europeans, who previously settled for the first time in the area east of the Company's (VOC) fortress (Vredeburg). The first settlement later also extended to the east of the Code River, and is now known as Bintaran.